MENINGKATKAN HASIL BELAJAR MATERI BENDA TUNGGAL DAN CAMPURAN MENGGUNAKAN KOMBINASI MODEL PBL, NHT & MM - Radiansyah; Elsa Amalia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the students’ learning outcomes, describes the educators’ activities and increases the students’ learning activities by using combination models of problem-based learning (PBL), numbered heads together (NHT), and make a match (MM). The research method used a quantitative and qualitative approach with the Classroom Action Research (CAR), which was conducted in four meetings. The subjects of the research involved 26 fifth-grade students at SDN Handil Bakti in the academic year 2021/2022. Data of students’ learning outcomes were obtained through measurement techniques with individual written tests. Educators’ and students’ activities were obtained by using observation sheets. Data analysis of the research used descriptive analysis techniques described by using tables, graphs, and interpretations with percentages. The results showed that 96% of students' learning outcomes were complete. Educator activity obtained a score of 27 with very good criteria, and 96% of students’ learning activity reached the very active category. In conclusion, the learning has been effective. The educators’ activities are very good and the students’ activities were very active. In addition, the students’ learning outcomes of single and mixed object learning materials have reached the needed completeness.